Optimalisasi Kawasan Strategis Prioritas (KSP) Menuju Kesejahteraan Berkelanjutan di Jawa Tengah: Pendekatan System-GMM - FX Gugus Febri Putranto; Christiayu Natalia (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
Evaluation of poverty alleviation and inequality issues to achieve sustainable prosperity requires in-depth analysis at a regional level. The establishment of Provincial Strategic Areas (KSP) in Central Java is expected to be a solution to accelerate the achievement of sustainable prosperity. This study aims to (1) analyze the determinants of poverty levels in each KSP region in the 2014-2023 period, in the short and long term; and (2) analyze the convergence of poverty levels and the speed of adjustment of disparities between regions in each KSP region. The results of dynamic panel regression modeling using the System Generalized Method of Moment (System-GMM) method can provide an in-depth analysis of targeted research-based policy recommendations in each Provincial Strategic Area (KSP) by offering recommendations for driving and inhibiting factors for poverty alleviation, to the time required to achieve convergence in reducing disparities between regions.